Neurosurgical Versus Neuromodulation in Writer’s Cramps: A Narrative Review - Yaqoob, Uzair; Hammad Ajmal, Muhammad; Ghimire, Samir; Paudel, Sumitra; Ghimire Karki, Shristee; Razak, Sufyan; Tanwir Awan, Tabeer (Cerrahpaşa Medical Journal, 2023)
The authors here reviewed the neurosurgical treatment and neuromodulation techniques used for writer’s cramps. The basic aim of this review is to shed a light on the current and previous research done for treating writer’s cramp. Surgical treatments and deep brain stimulation has been examined in many trials, with positive results. However, sample sizes in the studies were not large, and higher sample sizes in future studies may help research- ers better understand how these treatments work in writer’s cramps. Furthermore, procedures are frequently required to alleviate writer’s cramps incapacitating effects. Although research has shown that many neurorehabilitation and neuromodulation procedures are effective, most of the studies that evaluated these types of techniques had small sample sizes, limiting their widespread adoption. It is important to remember that these therapies necessitate a personalized approach. There is a requirement for multiple trials with the incorporation of various techniques to determine one treat- ment method that is most reliable and safe for a patient. Surgical treatments for treating writer’s cramps such as magnetic resonance-guided targeted ultrasonic thalamotomy, is good for patients suffering from extreme disabling effects, but it comes with the expense of severe side effects. Recent research on neuromodulation, behavioral methods, and sensorimotor training in the treatment of writer’s cramps has yielded encouraging results with few adverse effects, but more research is needed before these interventions can be adopted in practice. Cite this article as: Yaqoob U, Hammad Ajmal M, Ghimire S, et al. Neurosurgical versus neuromodulation in writer’s cramps: A narrative review. Cerrahpaşa Med J. 2023;47(2):112-117.